Playgrounds : Urban theatrical culture in Shakespeare's England and Golden Age Spain - Amelang, David J. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book compares the theatrical cultures of early modern England and Spain and explores the causes and consequences not just of the remarkable similarities but also of the visible differences between them. An exercise in multi-focal theatre history research, it deploys a wide range of perspectives and evidence to recreate the theatrical landscapes of these two countries and thus better to understand how the specific conditions of performance actively contributed to the development of each country's dramatic literature. This monograph develops an innovative comparative framework within which to explore the numerous similarities, as well as the notable differences, between early modern Europe's two most prominent commercial theatre cultures. By highlighting the nuances and intricacies that make each theatrical culture unique while never losing sight of the fact that the two belong to the same broader cultural ecosystem, its dual focus should appeal to scholars and students of English and Spanish literature alike, as well as those interested in the broader history of European theatre. Learning from what one 'playground' - that is, the environment and circumstances out of which a dramatic tradition originates - reveals about the other will help solve not only the questions posed above, but also others that still await examination. This investigation will be of great interest to students and scholars in theatre history, comparative drama, early modern drama, and performance culture"--
Keywords: English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; English drama -- 17th century -- History and criticism; Spanish drama -- Classical period, 1500-1700 -- History and criticism; Theater -- England -- History -- 16th century; Theater -- England -- History -- 17th century; Theater -- Spain -- History -- 16th century; Theater -- Spain -- History -- 17th century; English drama -- Spanish influences; Spanish drama -- English influences; PERFORMING ARTS / Theater / History & Criticism; PERFORMING ARTS / Theater / Playwriting; PERFORMING ARTS / Theater / Stagecraft